Barriers, access and management of paediatric epilepsy with telehealth. (April 2022) - Gali, Kari; Joshi, Sucheta; Hueneke, Sarah; Katzenbach, Alexis; Radecki, Linda; Calabrese, Trisha; Fletcher, Linda; Trandafir, Cristina; Wilson, Carey; Goyal, Monisha; Wusthoff, Courtney J; Le Pichon, Jean-Baptiste; et al.
Access to paediatric neurology care is complex, resulting in significant wait times and negative patient outcomes. The goal of the American Academy of Pediatrics National Coordinating Center for Epilepsy's project, Access Improvement and Management of Epilepsy with Telehealth (AIM-ET), was to identify access and management challenges in the deployment of telehealth technology. AIM-ET organised four paediatric neurology teams to partner with primary-care providers (PCP) and their multidisciplinary teams. Telehealth visits were conducted for paediatric epilepsy patients. A post-visit survey assessed access and satisfaction with the telehealth visit compared to an in-person visit. Pre/post surveys completed by PCPs and neurologists captured telehealth visit feasibility, functionality and provider satisfaction. A provider focus group assessed facilitators and barriers to telehealth. Sixty-one unique patients completed 75 telehealth visits. Paired t-test analysis demonstrated that telehealth enhanced access to epilepsy care. It reduced self-reported out-of-pocket costs ( p <0.001), missed school hours ( p <0.001) and missed work hours ( p <0.001), with 94% equal parent/caregiver satisfaction. Focus groups indicated developing and maintaining partnerships, institutional infrastructure and education as facilitators and barriers to telehealth. Telehealth shortened travelling distance, reduced expenses and time missed from school and work. Further, it provides significant opportunity in an era when coronavirus disease 2019 limits in-person clinics.